Analiza bazy PsycARTICLES pod kątem tytułów przypisanych do słowa kluczowego „bibliotherapy” - Chatzipentidis, Kiriakos (2016)
The article will examine PsycARTICLES database titles assigned to the keyword „bibliotherapy”. There will be presented the bibliography of bibliotherapeutic literature available in PsycARTICLES database.
Keywords: bibliotherapy literature; bibliotherapy research; bibliotherapy; PsycARTICLES